An optimized work-flow to reduce time-to-detection of carbapenemase-producing Enterobacteriaceae (CPE) using direct testing from rectal swabs. Issue 3 (4th May 2017) - O'Connor, C.; Kiernan, M. G.; Finnegan, C.; O'Hara, M.; Power, L.; O'Connell, N. H.; Dunne, C. P.
ABSTRACT: Rapid detection of patients with carbapenemase-producing Enterobacteriaceae (CPE) is essential for the prevention of nosocomial cross-transmission, allocation of isolation facilities and to protect patient safety. Here, we aimed to design a new laboratory work-flow, utilizing existing laboratory resources, in order to reduce time-to-diagnosis of CPE. A review of the current CPE testing processes and of the literature was performed to identify a real-time commercial polymerase chain reaction (PCR) assay that could facilitate batch testing of CPE clinical specimens, with adequate CPE gene coverage. Stool specimens (210) were collected; CPE-positive inpatients (n = 10) and anonymized community stool specimens (n = 200). Rectal swabs (eSwab™) were inoculated from collected stool specimens and a manual DNA extraction method (QIAamp® DNA Stool Mini Kit) was employed. Extracted DNA was then processed on the Check- Direct CPE® assay. The three step process of making the eSwab™, extracting DNA manually and running the Check-Direct CPE® assay, took <5 min, 1 h 30 min and 1 h 50 min, respectively. It was time efficient with a result available in under 4 h, comparing favourably with the existing method of CPE screening; average time-to-diagnosis of 48/72 h. Utilizing this CPE work-flow would allow a 'same-day' result. Antimicrobial susceptibility testing results, as is current practice, would remain a 'next-day' result. In conclusion, the Check- Direct CPE® assay was easily integrated into a local laboratory work-flow and could facilitate a large volume of CPE screening specimens in a single batch, making it cost-effective and convenient for daily CPE testing.